Injection laryngoplasty in the treatment of vocal cord sulcus vocalis - Manal A Bukhari; Mariam S Al-Amro; Sami E Al Harethy; Khalid H Malki; Tamer A Mesallam; Mohamed Farahat (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective is to review all cases of sulcus vocalis that were treated surgically with injection laryngoplasty and study their demographic data, ways of presentation, endoscopic evaluation, modality of treatment, and voice outcome. Materials and Methods: This is a retrospective study of 60 patients with sulcus vocalis who were treated surgically at King Abdulaziz University Hospital, King Saud University. The collected data included information on gender, age, symptoms, time of onset, endoscopic examination, surgical management, and voice outcome. Results: A total of 60 patients were included in this study, of which 53.3% were male and 46.7% were female. The mean age was 27.4 (11.06 standard deviation). Childhood presentation was positive in 61.7% of the cases and 8.3% had family history. There was a significant improvement in postoperative glottal gap and voice handicap index (VHI) after injection laryngoscopy and there were many positive significant correlations. The first correlation was between the preoperative and postoperative glottal gap (Spearman rank correlation coefficient r = 0.368). The second was between preoperative VHI and postoperative glottal gap (Spearman rank correlation coefficient r = 0.595). The third was between preoperative and postoperative VHI (Spearman rank correlation coefficient r = 0.832). The follow-up period ranged from 6 months to 5 years. Conclusion: Injection laryngoplasty is a promising surgical modality of treatment for sulcus vocalis, which shows significant improvement in voice outcome postoperatively. The management is still challenging and there is still no unified method for treating such condition.